Performance of Agro based Industry in India: Examining the Impact of Rural Development Policies on Agro Based Industry in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The quantity of persons who are very poor. Exceptional development in certainunderdeveloped nations makes it possible to achieve that objective internationally. One of the mostcrucial elements for the expansion of the Indian economy is rural development. India is mostly anagricultural nation. In India, the contribution of agriculture to GDP is over one-fifth. The government ofIndia has planned numerous projects related to rural development in order to boost the growth ofagriculture. India's top organization for developing policies, rules, and laws relating to the developmentof the rural sector is the Ministry of Rural Development. The main industries that contribute to the ruraleconomy and business include agriculture, handicrafts, fishery, poultry, and dairy. therefore givesbusinesses in the tiny area extra subsidies. This results in a greater number of businesses in the areawith fewer customers than proportional voting. Therefore, majoritarian elections are dominated byproportional voting